Catalytic oxidation of pulping effluent by activated carbon-supported heterogeneous catalysts. Issue 8 (17th April 2016) - Yadav, Bholu Ram; Garg, Anurag
ABSTRACT: The present study deals with the non-catalytic and catalytic wet oxidation (CWO) for the removal of persistent organic compounds from the pulping effluent. Two activated carbon-supported heterogeneous catalysts (Cu/Ce/AC and Cu/Mn/AC) were used for CWO after characterization by the following techniques: temperature-programmed reduction, Fourier transform infrared spectroscopy and thermo-gravimetric analysis. The oxidation reaction was performed in a batch high-pressure reactor (capacity = 0.7 L) at moderate oxidation conditions (temperature = 190°C and oxygen pressure = 0.9 MPa). With Cu/Ce/AC catalyst, the maximum chemical oxygen demand (COD), total organic carbon (TOC) and lignin removals of 79%, 77% and 88% were achieved compared to only 50% removal during the non-catalytic process. The 5-day biochemical oxygen demand (BOD5 ) to COD ratio (a measure for biodegradability) of the pulping effluent was improved to 0.52 from an initial value of 0.16. The mass balance calculations for solid recovered after CWO reaction showed 8% and 10% deduction in catalyst mass primarily attributed to the loss of carbon and metal leaching. After the CWO process, carbon deposition was also observed on the recovered catalyst which was responsible for around 3–4% TOC reduction.